Single-Cell Analysis Identify Transcription Factor BACH1 as a Master Regulator Gene in Vascular Cells During Aging - Ge, Fei; Pan, Qi; Qin, Yue; Jia, Mengping; Ruan, Chengchao; Wei, Xiangxiang; Jing, Qing; Zhi, Xiuling; Wang, Xinhong; Jiang, Lindi; Osto, Elena; Guo, Jieyu; et al. (Frontiers in Cell and Developmental Biology, 2021)
Vascular aging is a potent driver of cardiovascular and cerebrovascular diseases. Vascular aging features cellular and functional changes, while its molecular mechanisms and the cell heterogeneity are poorly understood. This study aims to 1) explore the cellular and molecular properties of aged cardiac vasculature in monkey and mouse; 2) demonstrate the role of transcription factor BACH1 in the regulation of endothelial cells (ECs) senescence and its mechanisms. Here we analyzed published single-cell RNA sequencing (scRNA-seq) data from monkey coronary arteries and aortic arches and mouse hearts. We revealed that the gene expression of YAP1, insulin receptor and VEGF receptor 2 was downregulated in both aged coronary arteries’ ECs of monkey and aged cardiac capillary ECs of mouse, and proliferation-related cardiac capillary ECs was significantly decreased in aged mouse. Increased interaction of ECs and immunocytes was observed in aged vasculature of both monkey and mouse. Gene regulatory networks analysis identified BACH1 as a master regulator of aging related genes in both coronary and aorta ECs of monkey and cardiac ECs of mouse. The expression of BACH1 was upregulated in aged cardiac ECs and aortas of mouse. BACH1 aggravated endothelial cell senescence under oxidative stress. Mechanistically, BACH1 occupied at regions of open chromatin and bound to CDKN1A (encoding for P21) gene enhancers, activating its transcription in senescent human umbilical vein endothelial cells (HUVECs). Thus, these findings demonstrate that BACH1 plays an important role in endothelial cell senescence and vascular aging.